INFLUENCE OF WORK SECTIONS ON COMMERCIAL BANK EMPLOYEES’WORK-FAMILY STRAIN EXPERIENCE IN ENUGU STATE - Ugwu, D.I (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2023)
The study was aimed at examining the influence of work sections on commercial bank employees’ work-family strain experience in Enugu State. Four hundred and seventy seven employees of the commercial banks were drawn by means of random sampling technique to participate in the study (204 from operation, 49 from info-tech, 123 marketing and 101 internal controls). Two instruments were used to generate information for the study. The first instrument was the Work-family Strain Inventory questionnaire that taped information on employees’ work-family strain experience. The second instrument was the Key Informant Interview Schedule (KIIS) used to generate qualitative datafor the study. It was hypothesized that employees ’work sections would not influence their levels of work-family strain experience. Data collected were analysed using Mean scores, Standard Deviation, One- Way Analysis of Variance (ANOVA) and Scheffe test. The finding revealed that employees of the info-tech and internal control sections reported moderate levels of strain experience while those in the marketing and operation sections reported low level strain experience. The result of the ANOVA further revealed significantly higher levels of strain experience among employees in the info-tech and marketing sections than their counterparts in operation and internal control sections of " the bank. Following from this finding, the researcher recommended among others that management of the banking industry should try to adopt appropriate work-family friendly intervention strategies that will be suitable for employees in various sections of the bank in balancing their work and family demands.